Giant isolated intracardiac thrombus presenting as acute heart failure secondary to right ventricular outflow tract obstruction in a patient with renal carcinoma. Issue 6 (11th June 2018) - Ballo, Piercarlo; Fibbi, Veronica; Granelli, Massimo; Fusco, Francesca; Abbondanti, Alessandro; Fantini, Andrea; Bartalini, Mattia; Consalvo, Matteo; Fazi, Antonio; Santoro, Giovanni M
Abstract: Right-sided intracardiac thrombi are potential causes of right ventricular (RV) failure, particularly when tricuspid or pulmonary obstruction occurs. In most cases, RV thrombus develops in patients with RV dysfunction and concomitant thrombosis in the systemic veins. However, RV thrombosis can rarely present as an isolated mass and despite preserved RV function, particularly in patients with thrombophilic states. In this report, we describe an unusual case of giant isolated RV thrombus presenting with acute RV failure secondary to dynamic RV outflow tract obstruction in a patient with renal carcinoma. Bedside echocardiography allowed a rapid assessment of the hemodynamic effects of the mass. The possibility of a thrombotic RV outflow obstruction should be considered in patients with acute RV failure, even in those with no evidence of thrombosis in the venous district. This may be particularly important in patients with prothrombotic states, where the effectiveness of routine thromboembolic prophylaxis could be reduced.